Exploring animal breeding through the lenses of authoritarian and liberal eugenics: why some breeding practices are wrong and what could be new ethical standards? - Louis-Maerten, Edwin (Frontiers in Animal Science, 2023)
Animal breeding is a mainstay of our relationship with domesticated species. However, it is sometimes leading to serious health and welfare issues, such as canine brachycephaly or double-muscling phenotype in Belgian Blue cattle. How then can we re-think our breeding system in animals? In this paper, I discuss the ethics of domestic animal breeding and new ways to achieve it. In doing so, I focus primarily on the concept of eugenics and its two major accounts: authoritarian and liberal eugenics. Indeed, the debates surrounding eugenics in humans is a quite prolific framework to question how we can justify animal breeding and has the merits to clarify the conditions needed to consider some practices as morally wrong (e.g. in the case of authoritarian eugenics). I argue that pure-bred breeding is comparable in many ways with authoritarian eugenics primarily because it does not consider the benefits for the animals but external factors such as beauty, productivity or certain behaviors. But arguing so raises the question whether this renders all types of animal breeding unethical. I refute this conclusion and give some arguments to support an active use of more ethical kinds of breeding systems. Specifically, I explore the concept of liberal eugenics and its limitations to defend a breeding practice that is both liberal and responsible. Such new standards can warrant a focus on animal welfare and put forward the central role of breeders in this process.